Thresholds of Abnormality Perception in Facial Esthetics among Laypersons and Dental Professionals: Frontal Esthetics - Raed H. Alrbata; Ayham Kh. Alfaqih; Mohammad R. Almhaidat; Ahmad M. Al-Tarawneh (Hindawi Limited, 2020)
Aim. To find thresholds at which laypersons and dental professionals perceive abnormalities in two facial frontal esthetics variables: facial symmetry and vertical harmony. Materials and Methods. A baseline frontal image of a young male face with optimum facial proportions was generated from a real image using a photo editing software. Different facial asymmetry images were then generated from this image by manipulating the chin point position at 2 mm increment to the left side. Vertical harmony was perceived through manipulating lower anterior facial height (LAFH) at a ratio of 2% of increased and decreased heights. A total of 120 raters divided equally into four groups of laypersons, general dental practitioners (GDPs), orthodontists, and oral and maxillofacial surgeons (OMFSs) rated these images using an analog scale of 100 mm long. Using ANOVA and Tukey post hoc tests at P<0.05, the image that showed the first statistical difference compared to the baseline was considered as a threshold of abnormality. Results. The image of 4 mm asymmetry was defined by the laypersons and GDPs as the threshold of abnormality, while the orthodontists and OMFSs realized that at 2 mm. Laypersons and GDPs defined a threshold of 46% as an abnormal decrease in the LAFH and the other 2 groups at 48%. All dental professionals groups rated the image of 54% as an abnormal increase in the LAFH while laypersons perceived that at 56%. Conclusion. These thresholds regarding frontal esthetics may contribute to the process of establishing proper orthodontic treatment planning that suits the highest facial esthetic standards.